Circ_0005875 sponges miR-502-5p to promote renal cell carcinoma progression through upregulating E26 transformation specific-1. Issue 1 (January 2022) - Luo, Sheng; Deng, Fang; Yao, Nana; Zheng, Fu
Abstract : Increasing evidence has shown that circular RNAs (circRNAs) play critical roles in various cancers, including renal cell carcinoma (RCC). We aimed to explore the role and underlying mechanism of circ_0005875 in RCC. The expression levels of circ_0005875, microRNA-502-5p (miR-502-5p) and E26 transformation specific-1 (ETS1) mRNA were determined by quantitative real-time PCR. Cell proliferation was assessed by Cell Counting Kit-8, colony formation, and 5-Ethynyl-2′-deoxyuridine (EdU) assays. Cell migration and invasion were monitored by wound healing assay and transwell assay, respectively. Flow cytometry analysis was applied to determine cell apoptosis and cell cycle distribution. Western blot assay was performed to measure the protein expression of CyclinD1 and ETS1. The interaction between miR-502-5p and circ_0005875 or ETS1 was confirmed by dual-luciferase reporter and RNA immunoprecipitation assays. A xenograft tumor model was established to confirm the role of circ_0005875 in vivo . Circ_0005875 and ETS1 were upregulated and miR-502-5p was downregulated in RCC tissues and cells. Knockdown of circ_0005875 suppressed RCC cell proliferation, migration and invasion, and induced apoptosis and cell cycle arrest. MiR-502-5p was a target of circ_0005875, and miR-502-5p inhibition reversed the inhibitory effects of circ_0005875 knockdown on the malignant behaviors of RCC cells. ETS1 was a direct target of miR-502-5p, and miR-502-5p exerted its anti-tumor role in RCC cells by targeting ETS1. Moreover, circ_0005875 knockdown decreased ETS1 expression by sponging miR-502-5p. Additionally, circ_0005875 depletion suppressed tumor growth in vivo . Circ_0005875 knockdown suppressed RCC progression by regulating miR-502-5p/ETS1 axis, which might provide a promising therapeutic target for RCC.